Optimal fertilization in rainfed corn regarding nutrient removal and soil diagnosis in small plots - García-Martínez, René; González-Félix, Eduar Antonio; Ayllón-Benítez, Julio César; García-Urbina, Jesús; Sánchez-Aguilar, Hotón (Revista Mexicana de Ciencias Agrícolas, 2026)
In the south of the State of Mexico, Mexico, small corn producers obtain low yields (
Keywords: Zea mays; corn nutrition; corn production; fertilization costs; soil fertility